MANAGEMENT OF INDEPENDENT WORK OF STUDENTS IN EDUCATIONAL PROCESS (Pedagogy of Higher and Secondary Education, 2001)
The article deals with different forms of pupils’ individual activities while working with the textbook. Some recommendations are given on the problem of pedagogical leadership intended for pupils ’ educational individual work.